Asuhan Keperawatan Pada An.W Dengan Thalasemia Di Ruang Anggrek 2 RSUD dr. Soeselo Kabupaten Tegal - Naila Nabila; Esti Nur Janah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Thalassemia is an inherited hemolytic anemia caused by genetic abnormalities in chromosomes 11 and 16 that impair globin chain production, leading to insufficient hemoglobin and red blood cells. This study aims to describe nursing care for An. W with thalassemia at the Anggrek 2 Ward of RSUD dr. Soeselo, Tegal Regency. The method used was a descriptive approach through anamnesis, documentation, observation, and literature review. Nursing care was carried out over two days (January 13–14, 2026). Physical examination results on January 12, 2026 showed a pale face, anemic conjunctiva, weakness, CRT >3 seconds, decreased skin turgor, weak peripheral pulse, cold extremities, and laboratory hemoglobin of 5.9 g/dL, with vital signs of pulse 111x/minute, temperature 36.7°C, and respiration 22x/minute. Two nursing diagnoses were established: ineffective peripheral perfusion related to decreased hemoglobin concentration (D.0009), and activity intolerance related to weakness (D.0056). Nursing interventions included circulatory care (I.02079) and energy management (I.05178). Nursing implementation was carried out according to plan. Evaluation on January 14, 2026 showed that both nursing diagnoses were resolved; the patient's hemoglobin improved to 10.7 g/dL after two blood transfusions, and the patient was declared fit for discharge. It is recommended that hospitals establish support groups for thalassemia patients to provide adequate emotional and social support.